MENINGKATKAN ADVERSITY QUOTIENT SISWA MENGGUNAKAN AUTOGRAPH - Ely Syafitri; Sahat Saragih; E. Elvis Napitupulu; KMS. Muhammad Amin Fauzi; anim anim; Elfira Rahmadani; Syahriani Sirait; Ismail Hanif Batubara (Smart Education, 2022)
Abstract. This study aims to determine the difference in adversity quotient between students who learn to use the Autograph learning media and students who receive conventional learning. The formulation of the problem in this study is